Plan de marketing para la empresa “Fabricar” de la ciudad de Loja - Guamán Armijos, Héctor Iván (2016)
The present project of thesis denominated Plan of Marketing for the company to "MANUFACTURE" of the city of Loja ", it consists on determining a marketing plan that foments the development and growth of the company study object, this plan Marketing, it is guided to energize in an effective way the services of the company, which has been carried out beginning to determine the size of the sample for the gathering of important data by means of the application of 289 surveys at external clients and 7 to internal clients, also an interview to the Manager proprietor of the comercializadora of vehicles. The methodology used in the whole process of the present investigation the methods was used, historical, Deductive, Inductive, Analytic, Descriptive; likewise, it was appealed to the technical use of the following ones: Direct Observation, Interviews, It Interviews. For the development of the present investigative work several topics were approached that they were determined in the following way: Situational analysis of the comercializadora of vehicles which allowed to obtain a clear vision of the current reality of the comercializadora, analysis of the ambient macro or external factors of the comercializadora, for it of the following factors was analyzed: Economic, Social, Political technological, in a same way it was analyzed the 5 forces of Porter that whose pondered result 2,89, it could settle down that in the company it takes advantage of the opportunities and it minimizes the threats, in a same way you proceeded to carry out the internal analysis for it was applied it an interview to the gentleman manager and a series of surveys to the external clients and internal clients this information it was the support to determine main EFI it demonstrates us that the pondered result is 2,74 what demonstrates that the company takes advantage of its strengths and it minimizes its weaknesses. Once carried out the wombs so much internal as external main FODA was elaborated, which determines the strengths, opportunities, weaknesses and more outstanding threats that it possesses the company in study, this main FODA was good for the construction of the womb of High impact; and the technical determination of the crossings FO-FA-DO-GIVES, of these strategies the strategic objectives were determined that became the importance of the operative plans that you/they are constituted in the following way in its structure, goal, strategy, politics, tactics, activities, time, budget, responsible and prospective results. The elaboration of the operability plans designed for each strategic proposed objective comes to supplement the realization of the present Plan of Marketing When concluding the work they are the conclusions to those that he/she has been able to arrive and through them to the respective recommendations that it is given for the company study object